Pemetaan Geologi dan Identifikasi Sesar Aktif di Lokasi Calon Tapak PLTN Ketapang dan Sekitarnya, Madura - Ngadenin, Ngadenin; Subiantoro, Lilik; Widana, Kurnia Setiawan; Sutriyono, Agus; Widito, P. (BRIN Publishing, 2012)
The result of economical study about demand of water supply and electric in Madura Island concludes that in 2016 Madura Island will need nuclear desalination plant to process sea water becomes fresh water. In order to support the installation of nuclear desalination plant, it is required site free from active fault, because active fault is mainly rejection factor criteria on site selection process. Aim of the research is to get geological information and identify of active fault in the site candidate of nuclear desalination plant at Ketapang area and its surrounding by interpretation of aerial photograph and land sat imagery, geological and structure geological mapping as well as trenching. The lithology of Ketapang (Md.01) and Sokobana (Md.02) site candidate consists of reef and chalky limestone forming undulating hills morphology. Structurally, research area forms a monocline with East-West trending axis, plunging 10o to East, the direction of strike is West-East, dip 10o - 30o to North. Geological structure analysis show that research area is free from active fault.